Treatment of Chronic Hepatitis C in a Canadian Aboriginal Population: Results from the Prairie Study - Gerald Yosel Minuk; Meaghan O’Brien; Kim Hawkins; Didi Emokpare; James McHattie; Paul Harris; Lawrence Worobetz; Karen Doucette; Kelly Kaita; Stephen Wong; Gilles Pinette; Julia Uhanova (Canadian Journal of Gastroenterology)
BACKGROUND: The Aboriginal population of Canada is at increased risk of exposure to the hepatitis C virus (HCV). Previous data indicate that spontaneous clearance of HCV occurs more often in Aboriginals than Caucasians. Whether this enhanced response extends to antiviral therapy for chronic HCV remains to be determined.